2014
DOI: 10.1111/pops.12182
|View full text |Cite
|
Sign up to set email alerts
|

FightandFlight: Evidence of Aggressive Capitulation in the Face of Fear Messages from Terrorists

Abstract: In an era of digital technology and the Internet, terrorists can communicate their threats directly to citizens of Western countries. Yet no research has examined whether these messages change individuals' attitudes and behaviour, or the psychological processes underlying these effects. Two studies (conducted in 2008 and 2010) examined how American, Australian, and British participants responded to messages from Osama bin Laden that threatened violence if troops were not withdrawn from Afghanistan. Heightened … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 38 publications
2
9
0
Order By: Relevance
“…More specifically, Iyer et al. () showed that fear about terrorism predicts support for aggression only when there are few direct costs for the ingroup. In the present paper, we propose that fear is based in participants' view of terrorists as strong perpetrators, which indicates a formidable adversary who has the power to aggress again.…”
Section: Political Implications Of Emotional Responses To Terrorism Imentioning
confidence: 99%
See 2 more Smart Citations
“…More specifically, Iyer et al. () showed that fear about terrorism predicts support for aggression only when there are few direct costs for the ingroup. In the present paper, we propose that fear is based in participants' view of terrorists as strong perpetrators, which indicates a formidable adversary who has the power to aggress again.…”
Section: Political Implications Of Emotional Responses To Terrorism Imentioning
confidence: 99%
“…Such selfprotection may be achieved either by running away from the threat (i.e., flight; Roseman et al, 1994) or attempting to appease or mollify those responsible for the threat (Frijda et al, 1989;Iyer & Oldmeadow, 2006). Recent research (e.g., Iyer, Hornsey, Vanman, & Esposo, 2013;Spanovic, Lickel, Denson, & Petrovic, 2010) indicates that fearful individuals can be strategic in choosing a self-protective response. More specifically, Iyer et al (2013) showed that fear about terrorism predicts support for aggression only when there are few direct costs for the ingroup.…”
Section: Political Implications Of Emotional Responses To Terrorism Imentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, research on audiences who have been exposed to terrorist violence through traditional media show that media saturation following a terrorist attack can result in "mean world" syndrome whereby audiences overestimate the risk of becoming the victim of terrorism and demonstrate an irrational desire for overprotection (Matusitz 2012). This overreaction to negative emotions has been shown to manifest as a form of catastrophising in which audience members feel either increased aggression towards out-groups, particularly when they share the same religion or ethnicity as the terrorists (Kiper and Sosis 2015), or an opposite fear that encourages capitulation to terrorist demands (Iyer et al 2015). This ability of media exposure to terrorism to create fear, anxiety, anger, aggression, and prejudice towards an out-group has been shown to be more pronounced than in media about other forms of crime (Shoshani and Slone 2008;Nellis and Savage 2012).…”
Section: Emotions Terrorism and The Audiencementioning
confidence: 99%
“…In other words, the fear as to what might happen took over and resulted in the decline of the support. Numerous scholars of political and social psychology (Cheung-Blunden and Ju, 2016; Iyer et al, 2015; Thórisdóttir and Jost, 2011; Valentino et al, 2008) speak about the effect emotions have on politics and explicitly identify fear and anxiety as two emotions which hinder democratic political participation and yet commonly accompany perceptions of insecurity and terrorist threat. The change of attitude also coincides with the Supreme Court’s decision in Al-Adahi .…”
Section: The Symptom the Public And A Return Of The Repressedmentioning
confidence: 99%